Multiple and non-planar crack propagation analyses in thin structures using FCPAS (Fracture and Structural Integrity, 2015)
In this study, multiple and non-planar crack propagation analyses are performed using Fracture and Crack Propagation Analysis System (FCPAS). In an effort to apply and validate FCPAS procedures for multiple and non-planar crack propagation analyses, various problems are solved and the results are compared with data available in the literature. The method makes use of finite elements, specifically three-dimensional enriched elements to compute stress intensity factors (SIFs) without special meshing requirements. A fatigue crack propagation criterion, such as Paris-Erdo?an equation, is also used along with stress intensity factors to conduct the simulation. Finite element models are generated within ANSYS™ software, converted into and solved in FRAC3D program, which employs enriched crack tip elements. Having computed the SIFs for a given crack growth increment and using a growth criterion, the next incremental crack path is predicted and the fracture model is updated to reflect the non-planar crack growth. This procedure is repeated until cracks reach a desired length or when SIFs exceed the fracture toughness of the material. It is shown that FCPAS results are in good agreement with literature data in terms of SIFs, crack paths and crack growth life of the structure. Thus, accuracy and reliability of FCPAS software for multiple and non-planar crack propagation in thin structures is proven.
Keywords: Fracture; Nonplanar Crack Growth; Crack Propagation